Global outreach and networking promotion to accelerate tropical diseases elimination - Shan Lv; Xiao-Nong Zhou (BMC, 2024)
Abstract Cooperation and networking are powerful tools in the combating against tropical diseases. Cooperation on a global scale is essential due to the transboundary nature of tropical diseases. Networking plays a pivotal role in facilitating such cooperation. Both cooperation and networking can foster innovation in disease control programmes. Collaborative research can lead to the development of new drugs and vaccines, while shared surveillance data can enable the early detection and control of disease epidemics. Therefore, consensus of cooperation and networking has been reached during the 7th Symposium on Surveillance-Response Systems Leading to Tropical Diseases Elimination, which reflected in the two documents, i.e., Consensus for Transboundary Tropical Diseases Control, and Action Consensus of the Network of WHO Collaborating Centres Related to NTDs. These documents will improve the efforts in the fighting against tropical diseases through collective actions to achieve the United Nations' Sustainable Development Goals (SDGs). Graphical Abstract